Characterization of in vivo expanded OspA-specific human T-cell clones. - Ausubel, L; O'Connor, K; Baecher-Allen, C; Trollmo, C; Kessler, B; Hekking, B; Merritt, D; Meyer, A; Kwok, B; Ploegh, H; Huber, B; Hafler, D (2005)
A panel of CD4 T-cell clones was isolated from synovial fluid by single cell flow cytometry from a patient with treatment-resistant Lyme arthritis using a DRB1*0401 major histocompatibility complex (MHC) class II tetramer covalently loaded with outer surface protein A (OspA) peptide164-175, an immunodominant epitope of Borrelia burgdorferi. Sequencing of the T-cell receptors of the OspA reactive clones showed significant skewing of the T-cell receptor repertoire. Of the 101 T-cell clones sequenced, 81 possessed TCR beta chains that were present in at least one other clone isolated. Complete sequencing of both alpha and beta chains of a subset of clones showed that at least two distinct T-cell clones were expanded in vivo. Binding studies using a panel of Ala-substituted peptide ligands were performed to determine potential MHC binding sites of the OspAp164-175 to DRB1*0401. In addition, T-cell clones were tested functionally for their reactivity to the wild-type peptide as well as to altered peptide ligands (APLs) and peptide libraries based on the OspA epitope in order to determine the TCR contact residues and the stringency in T cell recognition. We are among the first to define the characteristics of TCR usage of T cells isolated from an inflamed immune compartment in an individual with an autoimmune disease potentially triggered by a microbial antigen.